Product level dataset on embodied human appropriation of net primary production - Nicolas Roux; Lisa Kaufmann; Sarah Matej; Thomas Kastner; Alberte Bondeau; Helmut Haberl; Karlheinz Erb (Data in Brief, 2023)
This dataset includes data on the embodied human appropriation of net primary production (eHANPP) associated with products derived from agriculture and forestry. The human appropriation of net primary production (HANPP) is an indicator of changes in the yearly availability of biomass energy from photosynthesis that remains available in terrestrial ecosystems after harvest, under current land use, compared to the net primary production of the potential natural vegetation. HANPP is an indicator of land-use intensity that is relevant for biodiversity and biogeochemical cycles. The eHANPP indicator allocates HANPP to products and allows tracing trade flows from origin (the country where production takes place) to consumption (the country where products are consumed), thereby underpinning research into the telecouplings in global land use. The datasets described in this article trace eHANPP associated with the bilateral trade flows between 222 countries. It covers 161 primary crops, 13 primary animal products and 4 primary forestry products, as well as the end uses of these products for the years 1986 to 2013.